2008
DOI: 10.1089/jmf.2007.549
|View full text |Cite
|
Sign up to set email alerts
|

Saengshik, a Formulated Health Food, Prevents Liver Damage in CCl4-Induced Mice and Increases Antioxidant Activity in Elderly Women

Abstract: Saengshik is a Korean noncooked food made with of more than 30 different whole gains, vegetables, fruits, mushrooms, and seaweeds. All of these ingredients are frozen and dried to minimize the loss of nutrients. Saengshik has become popular among health-conscious people in the Republic of Korea. The study aims to investigate antioxidant effects of Saengshik by in vivo and human experiments. In in vivo tests, mice were fed Saengshik for 4 weeks, and oxidative damage was induced by CCl(4). Then the effects of Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Pre-treatment with H. opuntia (80 mg/kg) led to 20 and 25% reductions in serum and liver TBARS levels, respectively. These results are in agreement with Kim et al, 35 who observed a comparable reduction in hydroperoxide levels in the liver and plasma (30 and 15%, respectively, relative to CCl 4treated group) in a study of rats fed on Saengshik, a non-cooked food containing vegetables and seaweeds. Similarly, a previous study from our laboratory showed that an H. incrassata aqueous extract was effective in reducing TBARS levels by 55% in rats with oxidative stress induced by methylmercury.…”
Section: Effect Of H Opuntia Extract On CCL 4 -Induced Liver Damage supporting
confidence: 92%
See 1 more Smart Citation
“…Pre-treatment with H. opuntia (80 mg/kg) led to 20 and 25% reductions in serum and liver TBARS levels, respectively. These results are in agreement with Kim et al, 35 who observed a comparable reduction in hydroperoxide levels in the liver and plasma (30 and 15%, respectively, relative to CCl 4treated group) in a study of rats fed on Saengshik, a non-cooked food containing vegetables and seaweeds. Similarly, a previous study from our laboratory showed that an H. incrassata aqueous extract was effective in reducing TBARS levels by 55% in rats with oxidative stress induced by methylmercury.…”
Section: Effect Of H Opuntia Extract On CCL 4 -Induced Liver Damage supporting
confidence: 92%
“…38 These results suggest potent hepatoprotective activity of the phenolic fraction of H. opuntia. Kim et al 35 observed a comparable rise in SOD activity in rats fed on Saengshik for 4 weeks. Mancini-Filho et al 34 reported considerable increase in the activities of SOD and CAT in rats treated with polyphenol-rich fractions (80 mg/kg) of H. monile.…”
Section: Effect Of H Opuntia Extract On CCL 4 -Induced Liver Damage mentioning
confidence: 81%
“…It has also been shown to have higher nutritional value [ 3 ] and had a greater anti-inflammatory effect than Sunsik in our study. Several studies have reported that Saengshik has protective effects on carbon tetrachloride (CCl 4 )-induced protein oxidative damage in mouse liver, and other health benefits, such as anti-diabetes, anti-hyperlipidemia, anti-obesity, immune enhancement, anti-oxidative, detoxifying, fatty liver improving, and other effects in human and animal studies [ 4 5 6 7 8 9 10 11 ]. Natural raw meal (NRM), called raw meal in America, which is regarded as a natural health food, contains high levels of freeze-dried fresh whole grains, vegetables, and berries instead of legumes due to high allergic score [ 12 ], which is a critical difference between it and Saengshik manufactured in South Korea [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that saengshik had a hepatoprotective effect, against CCl 4 ‐induced hepatotoxicity (Kim and others 2007). Also, other researchers demonstrated an antioxidative effect of saengshik (Lee and others 2003a, 2003b; Kim and others 2008). Adom and Liu (2002) reported that various kinds of uncooked whole grains have great antioxidative activity by phytochemical compound, especially in the bound form.…”
Section: Discussionmentioning
confidence: 85%